2021
DOI: 10.5152/tud.2020.20247
|View full text |Cite
|
Sign up to set email alerts
|

The associations of RENAL, PADUA and C-index nephrometry scores with perioperative outcomes and postoperative renal function in minimally invasive partial nephrectomy

Abstract: Ali Serdar Gözen, et al.; Robot-assisted vasovasostomy and vasoepididymostomy: Current status and review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 30 publications
0
15
0
2
Order By: Relevance
“…There are many studies investigating the nephrometry scores and PN outcomes. The external validation studies demonstrated that nephrometry scores associated with perioperative and renal functional outcomes (14)(15)(16)23). However, there are only four studies on comparative analysis of nephrometry scores to predict the Trifecta success (8,20,23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies investigating the nephrometry scores and PN outcomes. The external validation studies demonstrated that nephrometry scores associated with perioperative and renal functional outcomes (14)(15)(16)23). However, there are only four studies on comparative analysis of nephrometry scores to predict the Trifecta success (8,20,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The radius, exophytic/endophytic, nearness, anterior/posterior, location (RENAL) nephrometry score, preoperative aspects and dimensions used for an anatomic classifications (PADUA) score, and the centrality index (C-index) remain the most known and used systems (11)(12)(13). The importance of these nephrometry scores in predicting the perioperative and renal functional outcomes of PN has been demonstrated (14)(15)(16).…”
Section: Introductıonmentioning
confidence: 99%
“…(r = 0.29 [0.17, 0.44]; I 2 = 0.0%, p = 0.51) and PADUA (r = 0.24 [0.10, 0.38]; I 2 = 15.5%, p = 0.277). Moreover, a pooled analysis of Cindex score yielded a stronger relationship with ACE evaluated by radionuclide GFR than the other two (r = −0.49 [−0.87, −0.11]; I 2 = 91.9%, p < 0.001) (Figure7).3.2.5 | Length of stayLOS was reported by six studies 17,18,21,28,29,32. Compared with the other two scores, A pooled analysis of PADUAscore showed no statistically significant correlation with LOS (r = 0.16 [−0.00, 0.31], p > 0.05; I 2 = 27.5%, p = 0.029), while R.E.N.A.L.…”
mentioning
confidence: 94%
“…Estimated blood loss EBL was reported by eight studies 18,19,21,23,24,28,29,32. A Correlation between three nephrometry scores and estimated blood loss…”
mentioning
confidence: 99%
See 1 more Smart Citation